The Challenges of Assessing Spiritual Intelligence in Islamic Education: Between Cognitive and Affective Aspects - Azhar Azhar; M. Ikhwanul Hakim; Hizbul Wathoni (LPPM Institut Pendidikan Nusantara Global, 2026)
The aim of this study is to analyze the challenges of assessing spiritual intelligence in Islamic Religious Education, focusing on the gap between cognitive and affective-spiritual aspects. The research uses a qualitative case study approach through interviews, observations, and document analysis. The findings show that assessment practices are still dominated by cognitive methods such as written tests, memorization, and oral examinations, while aspects of attitude, worship, and character are difficult to measure objectively. As a result, students demonstrate sufficient religious knowledge but lack spiritual and moral maturity. The study recommends developing holistic assessment instruments, providing teacher training, and utilizing digital technology to support more balanced assessment of knowledge and spiritual intelligence.